1993
DOI: 10.1038/362333a0
|View full text |Cite
|
Sign up to set email alerts
|

Isotopic evidence for the source of lead in Greenland snows since the late 1960s

Abstract: IN 1969, Murozumi et al. demonstrated that the concentration of lead in Greenland snow had increased by a factor of 200 since ancient times, and concluded that most of this increase was a result of the use of alkyl-leaded petrol. Partly because of these findings, the United States and other western countries limited the use of lead additives in petrol from about 1970. Recently, Boutron et al. showed that the lead concentration in Greenland snow had decreased by a factor of ∼7.5 over the past 20 years, and sugg… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

6
88
1
8

Year Published

1998
1998
2017
2017

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 214 publications
(103 citation statements)
references
References 15 publications
6
88
1
8
Order By: Relevance
“…Additionally, diffuse pollution by wet and dry deposition has resulted in the long-term 60 accumulation of heavy metals in many parts of the world, for example in Greenland ice 61 (Rosman et al, 1993), peat bogs (Weiss et al, 1999) and remote Alpine and subarctic soils 62 is then defined by (Chadwick et al, 1990): 237 j,w w C j,w p C j, p i,w 1 1 (4) 238 where C j,p (kg/t) is the concentration of element j in protolith (e.g., unweathered parent 239 material, bedrock) and C j,w is the concentration of element j in the weathered product (kg/t). 240…”
Section: Introduction 50mentioning
confidence: 99%
“…Additionally, diffuse pollution by wet and dry deposition has resulted in the long-term 60 accumulation of heavy metals in many parts of the world, for example in Greenland ice 61 (Rosman et al, 1993), peat bogs (Weiss et al, 1999) and remote Alpine and subarctic soils 62 is then defined by (Chadwick et al, 1990): 237 j,w w C j,w p C j, p i,w 1 1 (4) 238 where C j,p (kg/t) is the concentration of element j in protolith (e.g., unweathered parent 239 material, bedrock) and C j,w is the concentration of element j in the weathered product (kg/t). 240…”
Section: Introduction 50mentioning
confidence: 99%
“…Subsequently, Rosman and his colleagues at Curtin University extended these studies by measuring the isotopic composition of Pb in polar ice cores as a function of time, and showed that sources of Pb pollution can be traced to their origin in both modern and ancient environments. 144 A new advanced ultraclean environment (ACE) laboratory has recently been constructed at Curtin University, in which ice cores can be decontaminated and prepared for sensitive mass spectrometric analysis. This will enable higher sensitivities to be attained than in the past.…”
Section: A Renewal Of Geological Mass Spectrometry In Western Australiamentioning
confidence: 99%
“…To date studies have focused extensively on the use of Pb isotopes as an environmental tracer in a wide range of media, including air and aerosols [117][118][119][120][121][122], snow and ice [123][124][125][126][127], soils [128][129][130][131][132], lacustrine and reservoir deposits [133][134][135][136], wetlands and peat [137][138][139][140], plants, mosses, and tree rings [141][142][143], human tissues and blood [121,144,145] and other biota [146][147][148][149][150][151][152]. Within riverine environments there is little question that the isotopes of Pb have been most extensively utilized as an isotopic tracer in forensic investigations (see Bird [29] for a detailed review of Pb as a contaminant tracer in rivers).…”
Section: Pb Isotopesmentioning
confidence: 99%